2009
DOI: 10.1111/j.1741-1130.2009.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience in Cambodia With the Use of a Culturally Relevant Developmental Milestone Chart for Children in Low‐ and Middle‐Income Countries

Abstract: The awareness and knowledge of developmental milestones among health practitioners need to be enhanced to better enable early identification and intervention with children who have delays in development, intellectual deficit, and developmental disabilities and are residents in low‐and middle‐income countries. To meet this end, a simple one‐page check‐off developmental milestone chart for age groups birth to eight years was developed as an outgrowth of a training program for pediatricians in Cambodia. Expected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…A surveillance instrument of this type was used in a trial in Cambodia to alert, remind, and sensitize health workers of relevant developmental milestones using a simple check‐off sheet grouped by age intervals 69 . Possible future refinement of the Cambodia milestones selected would be based on recent doctoral work 70 .…”
Section: Feasibility Of Early Detection and Intervention In Limcmentioning
confidence: 99%
“…A surveillance instrument of this type was used in a trial in Cambodia to alert, remind, and sensitize health workers of relevant developmental milestones using a simple check‐off sheet grouped by age intervals 69 . Possible future refinement of the Cambodia milestones selected would be based on recent doctoral work 70 .…”
Section: Feasibility Of Early Detection and Intervention In Limcmentioning
confidence: 99%
“…in the initial screening had proved problematic in other countries (Durkin et al, 1994;Zaman et al, 1990), while the next stage assumed the existence of an extensive corpus of trained professionals, such as psychologists, developmental paediatricians, audiologists, optometrists, and so forth, who could conduct sophisticated assessments, using culturally appropriate tools. In his study of the reliability of an easy-to-use developmental milestone chart to identify children with development delays in Cambodia modified from screening tools used in the West, Scherzer (2009) noted that what constitutes "delay" in one culture may not in another and recommended the need for more accurate, locally identified milestones. With services for children with disabilities being mainly in Phnom Penh and in some provincial capitals, assessments as the survey envisioned would either involve huge numbers of children coming to these centres or "mobile crews" of trained professionals following the survey enumerators.…”
Section: The Politics Of Disabilitymentioning
confidence: 98%
“…So all milestones do not occur at the same time for all children. A second assumption is that developmental milestones are the same universally (Scherzer, 2009). However, research has shown that mothers may identify other events in their child's life as a developmental milestone: In Cambodia, mothers spoke about "bat phneak", literally translated to "opening of the eyes" of their one-month-old babies.…”
Section: Challenges In Implementation Of Labeling and Identificationmentioning
confidence: 99%